2012
DOI: 10.1155/2012/574817
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Markers of Cardiovascular Disease in Rheumatoid Arthritis

Abstract: Cardiovascular (CV) disease is the most common cause of premature mortality in patients with rheumatoid arthritis (RA). It is the result of an accelerated atherosclerotic process. Both RA and atherosclerosis are complex polygenic diseases. Besides traditional CV risk factors and chronic inflammation, a number of studies have confirmed the role of genetic factors in the development of the atherogenesis observed in RA. In this regard, besides a strong association between the HLA-DRB1∗04 shared epitope alleles an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 135 publications
(147 reference statements)
2
33
0
1
Order By: Relevance
“…Since a growing body of evidence supports the notion of a genetic component in the risk of CVD in RA (for review, see ref. ), the potential association of rs662 variants with CVD in RA patients was further examined in some studies. Charles‐Schoeman and colleagues revealed that high PON‐1 activity (considered as either the R/R genotype or as serum PON‐1 activity) was protective against subclinical atherosclerosis development in RA.…”
Section: Discussionmentioning
confidence: 99%
“…Since a growing body of evidence supports the notion of a genetic component in the risk of CVD in RA (for review, see ref. ), the potential association of rs662 variants with CVD in RA patients was further examined in some studies. Charles‐Schoeman and colleagues revealed that high PON‐1 activity (considered as either the R/R genotype or as serum PON‐1 activity) was protective against subclinical atherosclerosis development in RA.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies exam ining the cardio vascular risk conferred by nonHLA alleles, such as TNF and other cytokineencoding genes, have had mixed results and, to date, the strongest genetic risk factors for cardiovascular mortality in RA are HLAassociated genes. 84 Disease phenotype RA is a heterogeneous disease with a range of outcomes for joint disease; the same variability is likely to apply to cardiovascular outcomes. A number of studies have found that risk of cardiovascular mortality is particularly increased in seropositive patients, 85,86 those with extra articular manifestations 87 (such as nodules) and those with higher levels of disability 86 (Box 2).…”
Section: Ra-related Factorsmentioning
confidence: 99%
“…Genetic association studies have suggested a role for ACP1 in human cardiovascular disorders [12][13][14][15]. LMPTP appears to modulate signalling through several tyrosine kinase receptors [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%